À la recherche d’une urbanité périphérique ? - Agathe Delebarre; Thomas Pfirsch (Territoire en Mouvement)
Recent studies have underlined the growing importance of small cities in the polarization processes in the outskirts of large metropolitan areas, and in the so-called “maturation” of periurban spaces. Some works have shown the importance of small cities as new economic central places or commercial amenities in urban outskirts. But their role in the periurban residential mobility patterns is largely unexplored. Based on a questionnaire survey in the Dunkerque metropolitan area (France), this paper analyses the key role of peripheral small cities in the housing career of periurban residents. First, we discuss the concept of « periurban small city ». Then, the field and the peculiarities of the Dunkerque region small cities are presented. Finally, we propose a typology of periurban residential careers, which shows that small cities tend to be attractive residential hubs within urban outskirts. We show that many periurban residents are attracted by the “minimal urbanism” small cities can offer, that is a compromise between an out of town relocation and a city-like dense living environment.